Design of Experimental Approach for the Quantification of Bictegravir, Content by Dissolution Method in Tablets Formulation Using RP-HPLC Method - Budda Ruthu Salomi; A. Shailaja; Mohammed Omar (International Journal of Allied Medical Sciences and Clinical Research, 2024)
In the current study the effort has been undertaken to improve most simple, economical, and sensitive and correct analytical HPLC method for the immediate valuation of these drugs without their prior separation. The method gives resolution with a short analysis time (< 25 min). The method parameter was validated and establishes to be simple, sensitive, accurate and precise. Percentage of recovery shows that the method is free from interference of the excipients used in the formulation. All the three ingredients were effectively resolved and quantified. The developed method reported herein was validated by parameters agreeing to ICH-Q2B guidelines. The offered method provided good system suitability, resolution, precision, accuracy, LOD and LOQ, linearity and robustness and requires less expensive reagents. The procedure designated now is simple, rapid, sensitive, selective and cost effective. It is apparent from the results that the suggested procedure is well suited for dissolution and assay and evaluation of drug, in dosage forms